Study of Antidote Activity of Zinc Ascorbate in Acute Mercury Lesions - A. A. Baranets; G. A. Prigorelov (Вестник войск РХБ защиты, 2023)
The article is dedicated to the study on the antidote activity of zinc ascorbate (С6Н8О4Zn) in acute mercury lesions. Biologically active zinc-containing substance – zinc ascorbate – is synthesized. It is determined that in case of acute mercury lesions the survival rates are much higher (from 10 to 67 %) for those experimental animals, which preliminarily have been treated with the therapeutic doses of zinc ascorbate, and their peripheral blood parameters (the percentage of dead leukocytes, the content of toxic granules in leukocytes, sulfhydryl groups in leukocytes and free sulfhydryl groups in blood serum) are close to the physiological norm. These data show that zync salt of ascorbic acid definitely can protect from toxic effects of mercury and can be used as a prophylactic antidote in case of the subsequent acute mercury lesion.